INVENTARISASI JENIS-JENIS TUMBUHAN DAN KESESUAIAN LAHAN UNTUK KONSERVASI DAERAH TANGKAPAN SUMBER MATA AIR ’WETIHU’ DESA BAUDAOK KECAMATAN TASIFETO TIMUR – BELU - Wahyu Widiyono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
District, East Nusa Tenggara Province. However, some wells in this area need to be conserved by planting of selected species at the watershed area in order the water available continually during a year. To understand the native and crop species that suitable to plant conservation the survey at the watershed of ‘Wetihu’, Baudaok-Belu was conducted in 2008. Aim of survey was to inventory the species and to understand land suitability based on its soil fertility and microclimate condition. Watershed landscape of ‘Wetihu’ in Baudaok Village, Belu District are characterized by rolling to hilly altitude,coral reef and limestone of soil material and the low soil fertility. Micro-climate in thisarea resulted the marginal land watershed and due to this problem the crop almost can not be planted by the local people. The observation by the distance of 1.5 km from ‘Baudaok’ well to the southern was found 39 wild and crop species. Some species which are able to adapt to the drought ecosystem and has potential to plant as economic crops are recommended to be selected, i.e.: the main food (Zea mays, Cajanus cajan), fruits (Musa paradisiaca, Mangifera indica), cattle feeding (Leucaene leucocephala, Sesbania grandiflora), handmade material (Bambusa sp.), fire wood, wind break trees and covercrops (Zizyphus mauritiana, Alstonia scholaris, Erythrina orientalis, Gmelina arborea,Schleichera oleosa), perfume oil producer (Santalum album).Key Words: native species, crops, watershed, conservation, Belu, East NusaTenggara Province